The Future of Learning: Integrating ChatGPT in Pakistan's Higher Education - Buriro, Maryam; Sethar, Waqar Ahmed; Parhyar, Amanullah (Annals of Human and Social Sciences, 2024)
The aim of this study is investigate the causes of using Generative AI Tools. GPT is a generative AI has started making inroads into higher education around the world, however, there is a debate around these AI tools special Generative -AI tools like ChatGPT. Using questionnaire survey the data was collected (b=151) from three universities located in Jamshoro, Sindh,. The finding shows the positive significant effect of behavioral intentions on the ChatGPT usage of the students with 78% variance explained by constructs like performance expectancy, effort expectancy, social influence, information quality, source trustworthiness, technical knowledge, facilitating conditions, however, behavioral intentions was not found to lead to actual usage of ChatGPT by the students with only weaker variance (14%) by behavioral intentions. This study recommends that while ChatGPT use can not be stopped at the campus, it is recommended that this may complemented and integrated in the higher education Institutions.